Occupational Health and Safety of Food Industry Employees with Emphasis on Specific Diseases - Stanislav MALÝ; Kristýna VAVREČKOVÁ; Klára MALME; Jozef KUBÁS; Katarína HOLLÁ; Linda MAKOVICKÁ OSVALDOVÁ (Communications of International Proceedings, 2021)
Musculoskeletal disorders are currently a highly debated topic and the subject of an OSHA EU campaign, as their severity is increasingly leading to incapacity for work and hospital admissions. Already in younger age groups, they pose significant problems for employees and employers alike. The article focuses on occupational safety and health with regard to the opinion of employees. Using the questionnaire method, the opinions of employees on the issue in the selected were found out. The results of the survey were compared and statistically evaluated so that the differences in the feelings of men and women could be found out. The survey was conducted in January 2021 in the Czech Republic in workplaces of the food and 294 employees participated. Aim of the article is to show the possibilities of monitoring and monitoring ergonomic risk factors, including the development of a final survey in some company workplaces of the food industry. Then point to out the sources of possible risks associated with the occurrence of a group of diseases related to nerves, tendons and supporting structures and to propose the application of proactive and reactive ergonomics measures to eliminate them.
Keywords: Occupational Health and Safety; Musculoskeletal Disorders; Ergonomic Risk Assessment; Human Resources; Enterprise Management.